Sighting of King Cobra Ophiophagus hannah in Sikkim, India: a new altitude record for the northeast - T. Bashir; K. Poudyal; T. Bhattacharya; S. Sathyakumar; J.B. Subba (Journal of Threatened Taxa, 2010)
We report the sighting of Ophiophagus hannah from Yuksam Village bordering Khangchendzonga Biosphere Reserve in Sikkim. The present record signifies a range extention for this species with respect to altitude (1,840m) and habitat (temperate forests) reported for this state and the northeast India.